140 COVID-19 is Associated with New Onset Erectile Dysfunction: Insights From a Multinational Registry. Issue 1 (1st April 2022) - Nackeeran, S; Chu, K; Masterson, T; Ramasamy, R
ABSTRACT: Introduction: As the COVID-19 pandemic has been ongoing since 2019, we are just beginning to see some of the short and long-term effects of infection. Vascular integrity is necessary for erectile function, and endothelial damage associated with COVID-19 is likely to affect the penile vasculature. Recent studies have showed evidence of COVID-19 virus within penile tissue through electron microscopy. We hypothesized that the COVID-19 infection may be a contributing factor to subsequent development of erectile dysfunction (ED). Objective: To determine if men with recent COVID-19 infection was associated with subsequent increased risk for development of erectile dysfunction. Methods: We assessed the risk of ED in men with COVID-19 in the United States (US) using the TriNetX Research Network, a federated EMR network of over 42 healthcare organizations and 66 million patients from the US, from 2009-2020. We identified adult men (≥18 years) with a recorded COVID-19 infection (ICD-10-CM B34.2, U07.1, U07.2, J12.81, J12.82, B97.29) since January 1, 2020 and compared them to an equivalent number of adult men who had COVID-19. Men with prior history or diagnosis of ED were excluded. We accounted for confounding variables through propensity score matching for age, race, body mass index (BMI), and history of the following comorbid medical conditions: diabetes mellitus (ICD-10-CM E11), hypertension (ICD-10-CM I10), or hyperlipidemia (ICD-10-CM E78). We assessed the association between COVID-19 and ED (ICD-10-CM N52) as a primary outcome through regression analysis with statistical significance assessed at p<.05. Results: Prior to propensity score matching, men with COVID-19 had an average age of 47.1 + 21.4 years, 13% had diabetes mellitus, and 27% had hypertension, while in men without COVID-19, average age was 42.4 + 24.3 years, 7% had diabetes, and 22% had hypertension. After propensity score matching, we compared 230, 517 men with COVID-19 to 232, 645 men without COVID-19 and found that COVID-19 diagnosis was significantly associated with ED (OR 1.120, 95% CI 1.004-1.248, p=0.0416). Strengths include large sample size and adjustment for confounding variables. Limitations include lack of data regarding ED (mild vs moderate vs severe) or COVID-19 infection severity. Conclusions: Our study showed that there is an increased risk of developing ED post-COVID infection, suggesting possible long-term effects due underlying endothelial dysfunction. The exact mechanism of how COVID-19 virus leads to erectile dysfunction remains to be elucidated. Disclosure: No